2011
DOI: 10.1007/s13233-011-0713-3
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible charcoal composites prepared by ionic liquids for drug detoxification

Abstract: Cellulose/charcoal and cellulose/heparin/charcoal composites were fabricated using ionic liquids to enhance the biocompatibility of charcoal and decrease the size of their active pores. Surface morphological studies of these biocompatible charcoal composites showed that their uniformly coated surfaces could inhibit the adsorption of proteins while allowing the removal of small drug molecules. The activated partial thromboplastin time demonstrated that heparinized surfaces on the cellulose/heparin/charcoal comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…9, 10 This cellulose-heparin-coated charcoal relied on a coating process utilizing a heparin imidazolium salt dissolved in a cellulose-containing room temperature ionic liquid and required extensive washing steps to remove the ionic liquid and convert the heparin imidazolium salt into the heparin sodium salt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9, 10 This cellulose-heparin-coated charcoal relied on a coating process utilizing a heparin imidazolium salt dissolved in a cellulose-containing room temperature ionic liquid and required extensive washing steps to remove the ionic liquid and convert the heparin imidazolium salt into the heparin sodium salt.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that cellulose–heparin-coated charcoal is capable of adsorbing hydrophobic protein-bound drugs without causing large losses of blood proteins. , This cellulose–heparin-coated charcoal relied on a coating process using a heparin imidazolium salt dissolved in a cellulose-containing room-temperature ionic liquid and required extensive washing steps to remove the ionic liquid and convert the heparin imidazolium salt into the heparin sodium salt.…”
Section: Introductionmentioning
confidence: 99%
“…ILs can be considered as good candidates for numerous chemical reactions, such as Diels-Alder reaction, Wittig reaction, Henry reaction, heterocyclic synthesis, and polymer synthesis. [17][18][19][20][21][22][23] Chiral center has an important role in biosystems, especially in biomacromolecules. The synthesis and application of these chiral materials are a considerable topic, which has been paid more attention in recent years.…”
Section: Introductionmentioning
confidence: 99%